BS17 Glycocalyx depth assessment in pig blood vessels for vein graft applications. (6th June 2022) - Tarassova, Nathalie; Butler, Matthew; Ascione, Raimondo; George, Sarah; Foster, Rebecca; Bond, Andrew
Abstract : Introduction: Human saphenous veins (hSV) are routinely used during coronary artery bypass grafting, however around 50% of grafted veins occlude 5–10 years post-surgery, often due to platelet aggregation and restenosis. All blood vessels are lined with endothelial cells which are coated in glycocalyx (eGlx), a gel-like layer of macromolecules at the interface between blood and the vessel wall, that have a role in mechanosensing blood flow, and preventing platelet aggregation. Direct comparisons between eGlx depth in different vessels could prove essential for future studies aiming to improve patency rates. Porcine arteriovenous graft models are used in translational studies to test bioengineered conduits, and it is therefore necessary to detect eGlx in this species. This study aims to screen lectins to optimise a staining protocol for eGlx, and then measure eGlx depth in venous and arterial porcine tissue, and in a pig arteriovenous graft model, to establish any differences between vessel types, and within the graft, which could influence their behaviour and longevity in the grafting environment. Methods and Results: Seven biotinylated lectins were assessed for eGlx staining specificity in formalin-fixed paraffin-embedded venous and arterial sections. Lycopersicon esculentum (tomato) (LEL) was deemed optimum, and fluorescent dual-staining with LEL and Octadecyl Rhodamine B Chloride (R18, for cell membranes) enabled confocal fluorescence imaging and peak-to-peak intensity profile analysis to be used as a measure of eGlx depth. The eGlx layer was significantly thicker in carotid arteries compared to jugular veins (301.5 ±33.8 nm vs. 242.3 ± 41.1 nm, p<0.05, n=6 per vessel). For the graft experiment, decellularised hSV were either seeded with porcine endothelial colony-forming cells or left unseeded as control, before being grafted into pig right carotid arteries for 4 weeks; only patent grafts were assessed for eGlx depth (n=4 and n=3 respectively). Seeded grafts had a significantly thicker eGlx in the proximal graft region (325.9 ±16.1 nm) compared to controls (240.8 ± 15.1 nm; p<0.01). Notably, control grafts had significantly reduced eGlx depth compared to its native proximal artery (p<0.05), while the seeded samples showed no difference. On average, native carotid arteries proximal to the graft had significantly increased eGlx depth compared to the distal arteries (315.5 ± 21.2 vs. 265.5 ± 35.5 nm, p<0.05, n=7). Conclusions: The confocal fluorescence profile peak-to-peak method was optimised here for the first time in large porcine vessels using LEL. The eGlx depth differences found between pig veins and arteries, as well as in native tissue and grafts, may influence the vein graft occlusion. The direct effect of eGlx thickness on graft long-term outcomes needs to be determined in further animal studies to assess whether eGlx graft management improves patency rates.